Chronic Adverse Drug Reactions of Phenytoin: A Comprehensive Review - Jamdade Sonali Lala; Ayodhya Tanaji Pardhe; Dr. V. N. Deshmukha; Dr. Rajesh Mandade (Asian Journal of Pharmaceutical Research and Development, 2025)
Phenytoin remains a cornerstone in the management of epilepsy and certain seizure disorders. However, its use is frequently complicated by a wide array of adverse drug reactions (ADRs) affecting multiple organ systems. This review aims to provide an in-depth overview of the chronic toxicities linked to phenytoin, discuss the underlying mechanisms, propose clinical management strategies, and highlight potential safer alternatives for long-term epilepsy management.